The impact of network size on bank branch performance - Hirtle, Beverly (Journal of Banking & Finance, 2007)
Despite significant technological innovation in retail banking services delivery, the number of US bank branches has grown steadily over time. Further, more and more of these branches are held by banks with large branch networks. This paper assesses the implications of these developments by examining measures of branch performance and asking how these measure vary across institutions with different branch network sizes. Our findings suggest that banks with mid-sized branch networks may be at a competitive disadvantage in branching activities. We find no systematic relationship between branch network size and overall institutional profitability, perhaps because banking organizations optimize the size of their branch network operations as part of an overall strategy involving both branch-based and non-branch-based activities.